The effect of psychological toughness and self-efficacy in the acquisition of the martial arts leg kick skill - Khodabandelou, M.; Salehian, M. H. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Aim. One of the applications of sport psychology is to help to improve performance, learn and implement skills. The main goal of this study was to determine the effect of psychological toughness and self-efficacy in the acquisition of the martial arts leg kick skill. Materials. The present research was practical in terms of purpose, and correlation in terms of nature. The statistical population was all the martial arts athletes in the city of Tabriz, some 1480 in 2020, of whom 305 were selected randomly based on the Cochran formula. In this study, three questionnaires: self-efficacy, psychological toughness and acquisition skills, and the skill of the leg kick were used in taekwando and karate to collect data. The data was analyzed using the SPSS 20 software, regression test. Results. The results showed that psychological toughness and self-efficacy play a significant role in the acquisition of the martial arts leg kick by combat athletes. Self-efficacy and mental toughness are the most important characteristics of a successful athlete. Conclusion. Athletes can have a positive effect on their performance by increasing mental toughness and self-efficacy.